Data Science and Artificial Intelligence for Statistics Education: Creating Smart Future of Teaching and Learning - Osuolale Peter Popoola; Dzaan Kumafan (ZBW - Leibniz Information Centre for Economics, 2025)
Integrating ~data science and artificial intelligence(AI) into statistics ~education have the potential to raise academic standards, improve the overall quality of statistics education. Data science is the "what" and "why" of student performance and learning patterns, and AI is the "how" the intelligent tools could be used in teaching and learning. Statistics plays vital roles in educational research, helping to understand student performance, identify trends, and evaluate the effectiveness of educational interventions. While statistical literacy, enabling individuals to critically evaluate information and make informed decisions. This paper outlines how data science and AI ~could be integrated into statistics education; Its impact to improve teaching and learning outcomes; addresses challenges, ethical and policy implications of integrating these technologies into statistics education.
Keywords: 330; Statistics; Statistics Education; Data Science; Artificial Intelligence